Epidemiology of injecting drug use, prevalence of injecting-related harm, and exposure to behavioural and environmental risks among people who inject drugs: a systematic review. Issue 5 (May 2023) - Degenhardt, Louisa; Webb, Paige; Colledge-Frisby, Samantha; Ireland, Jeremy; Wheeler, Alice; Ottaviano, Sophie; Willing, Alex; Kairouz, Abe; Cunningham, Evan B; Hajarizadeh, Behzad; Leung, Janni; Tran, Lucy T; et al.
Summary: Background: People who inject drugs are exposed to various and changing risk environments and are at risk of multiple harms related to injecting drug use (IDU). We aimed to undertake a global systematic review of the prevalence of IDU, key IDU-related harms (including HIV, hepatitis C virus [HCV], and hepatitis B virus [HBV] infection and overdose), and key sociodemographic characteristics and risk exposures for people who inject drugs. Methods: We systematically searched for data published between Jan 1, 2017, and March 31, 2022, in databases of peer-reviewed literature (MEDLINE, Embase, and PsycINFO) and grey literature as well as various agency or organisational websites, and disseminated data requests to international experts and agencies. We searched for data on the prevalence, characteristics, and risks of people who inject drugs, including gender, age, sexuality, drug-use patterns, HIV, HCV, and HBV infections, non-fatal overdose, depression, anxiety, and injecting-related disease. Additional data were extracted from studies identified in our previous review. Meta-analyses were used to pool the data where multiple estimates were available for a country. We present country, regional, and global estimates for each variable examined. Findings: We screened 40 427 reports published between 2017 and 2022, and the 871 eligible reports identified were added to the 1147 documents from the previous review. Evidence of IDU was documented in 190 of 207 countries and territories, and 14·8 million people (95% uncertainty interval [UI] 10·0–21·7) aged 15–64 years globally were estimated to inject drugs. Existing evidence suggests that there might be 2·8 million (95% UI 2·4–3·2) women and 12·1 million (95% UI 11·0–13·3) men who inject drugs globally, and that 0·4% (95% CI 0·3–1·3) of people who inject drugs identify as transgender. The amount of available data on key health and social risks among people who inject drugs varied widely across countries and regions. We estimated that 24·8% (95% CI 19·5–31·6) of people who inject drugs globally had experienced recent homelessness or unstable housing, 58·4% (95% CI 52·0–64·8) had a lifetime history of incarceration, and 14·9% (95% CI 8·1–24·3) had recently engaged in sex work, with substantial geographical variation. Injecting and sexual risk behaviour varied considerably geographically, as did risks of harms. Globally, we estimated that 15·2% (95% CI 10·3–20·9) of people who inject drugs are living with HIV, 38·8% (95% CI 31·4–46·9) have current HCV infection, 18·5% (95% CI 13·9–24·1) have recently overdosed, and 31·7% (95% CI 23·6–40·5) have had a recent skin or soft tissue infection. Interpretation: IDU is being identified in a growing number of countries and territories that comprise more than 99% of the global population. IDU-related health harms are common, and people who inject drugs continue to be exposed to multiple adverse risk environments. However, quantification of many of these exposure and harms is inadequate and must be improved to allow for better targeting of harm-reduction interventions for these risks. Funding: Australian National Health and Medical Research Council.